1970
DOI: 10.3329/jbcps.v27i2.4248
|View full text |Cite
|
Sign up to set email alerts
|

Management of Bronchiolitis with or without Antibiotics – A Randomized Control Trial

Abstract: Summary:Background: There has been epidemics of bronchiolitis in the recent years in Bangladesh. Bronchiolitis is mostly (95%) a viral disease in infants and young children but being treated with antibiotics in 99% of cases in our situation. Antibiotic has little role in the management of bronchiolitis. Very few randomized control trials without antibiotics in the management of bronchiolitis have so far been done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…This finding matches with other`s findings. 19,20,21 On the day of admission 100% children had rhonchi, after 4 day, about one-third of the total children had rhonchi; 36% of antibiotic group and 31% of without antibiotic group (p>0.5). After 4 days of admission 17% of antibiotic group and 14% of without antibiotic group had crepitation and 6 days after discharge 1(1%) child of without antibiotic group and 2(2%) from antibiotic group still had crepitation, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding matches with other`s findings. 19,20,21 On the day of admission 100% children had rhonchi, after 4 day, about one-third of the total children had rhonchi; 36% of antibiotic group and 31% of without antibiotic group (p>0.5). After 4 days of admission 17% of antibiotic group and 14% of without antibiotic group had crepitation and 6 days after discharge 1(1%) child of without antibiotic group and 2(2%) from antibiotic group still had crepitation, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…Few randomized control studies conducted so far on use of antibiotic in bronchiolitis, also found no evidence to support the use of antibiotics for bronchiolitis. 19,20,24,25 The cardinal radiological features of bronchiolitis are hyperinflation of the lung fields, increase interstitial markings and streaky opacities. Our experience is same, hypertranslucency in 74% and hyperinflation in 64% in cases.…”
Section: Discussionmentioning
confidence: 99%
“…In their randomized controlled study of 126 patients aged 1-2 months and hospitalized with viral bronchiolitis, Mazumder et al 14 divided their subjects into three groups -receiving IV ampicillin, oral erythromycin, or no antibiotics. No significant difference was observed between these three groups in terms of clinical findings (decreased respiratory difficulty, feeding difficulty, and respiration rate, and return of social smiling).…”
Section: Discussionmentioning
confidence: 99%
“…11 Reported outcomes of the use of antibiotics in acute viral bronchiolitis in previous studies include no significant difference in severity of symptoms (decreased respiratory difficulty, feeding difficulty, and respiration rate, or restoration of social smiling), no statistically significant difference in terms of mean length of hospital stay, and no acceleration of healing, while unnecessary antibiotic use was also described as a financial burden leading to iatrogenic side-effects and resistant microorganisms. [12][13][14][15] However, one study reported significant decreases in oxygen and intravenous fluid support requirements in patients receiving clarithromycin compared to placebo. The duration of beta-2 agonist use was also shorter in the clarithromycin group, and repeat hospitalization rates were lower.…”
Section: Introductionmentioning
confidence: 99%
“…Majumder et al. (24) recently conducted another study involving 104 children. While the study was conducted in one hospital, it was done across three groups: one received ampicillin, the other erythromycin and one group received no antibiotics.…”
Section: Discussionmentioning
confidence: 99%